Microstructure and Mechanical Behavior of Deep Drawing DC04 Steel at Different Length Scales - Schreijäg, Simone (KIT Scientific Publishing, 2013)
The deformation behavior of steels is strongly influenced by their microstructure which is a result of the alloying elements and thermal treatments. In this work, the microstructure and the deformation behavior of a non-alloyed deep drawing DC04 steel was investigated. The microstructure was analyzed during heat treatment by EBSD, then microcompression experiments were performed on selected microstructural units and then bulk steel samples were mechanically tested by tensile experiments.